Rethinking the Role of Value Communication in Business Corporations from a Sociological Perspective – Why Organisations Need Value-Based Semantics to Cope with Societal and Organisational Fuzziness - von Groddeck, Victoria (2011)
Why is it so plausible that business organisations in contemporary society use values in their communication? In order to answer this question, a sociological, system theoretical approach is applied which approaches values not pre-empirically as invisible drivers for action but as observable semantics that form organisational behaviour. In terms of empirical material, it will be shown that business organisations resort to a communication of values whenever uncertainty or complexity is very high. Inevitably, value semantics are applied in organisations first when the speakers are uncertain about which stakeholders to whom they have to address (uncertainty) or when different stakeholder groups have to be addressed simultaneously (complexity); second, when the identity of the organisation has to be described; and third, when future strategic options that cannot be expressed by quantitative terms have to be communicated. Values accordingly play a role in organisational practice when certain aspects are indeterminate. Therefore, they are a means for organisations to communicate under fuzzy circumstances. On the basis of these findings, new approaches to value management can now be formulated.
Keywords: value communication; value-based semantics; value-based management; System Theory; Sociology; Niklas Luhmann; Corporate Social Responsibility; Communication